Self-Regulation dan Zoom Fatigue pada Pengguna Media Video Conference - Walelang, Wedelyn Ericka Jeanette; Ambarwati, Krismi Diah (Universitas Muhammadiyah Metro, 2023)
The use of video conferencing media for a long time brings challenges in the form of fatigue that need to be understood and mitigated to maximize the benefits and impacts obtained. The hypothesis of this study is, there is a negative relationship between selfregulation and Zoom fatigue. This research method uses quantitative methods with the number of research participants is 409 students. The scales used are the Short SelfRegulation Questionnaire (SSRQ) and the Zoom Exhaustion and Fatigue (ZEF) Scale. The results showed that there was a significant negative relationship between selfregulation and Zoom fatigue in students using video conference media with a Pearson correlation value of -0.423 with sig. = 0.000 (p<0.05). It is known that Zoom fatigue experienced by students can be overcome if students have good self-regulation. So that fatigue from using video conferencing can be overcome and students are able to manage themselves properly during online activities.